Advances in in situ powder diffraction of battery materials: a case study of the new beamline P02.1 at DESY, Hamburg. (21st July 2013) - Herklotz, Markus; Scheiba, Frieder; Hinterstein, Manuel; Nikolowski, Kristian; Knapp, Michael; Dippel, Ann‐Christin; Giebeler, Lars; Eckert, Jürgen; Ehrenberg, Helmut
Abstract : A brief review of in situ powder diffraction methods for battery materials is given. Furthermore, it is demonstrated that the new beamline P02.1 at the synchrotron source PETRA III (DESY, Hamburg), equipped with a new electrochemical test cell design and a fast two‐dimensional area detector, enables outstanding conditions for in situ diffraction studies on battery materials with complex crystal structures. For instance, the time necessary to measure a pattern can be reduced to the region of milliseconds accompanied by an excellent pattern quality. It is shown that even at medium detector distances the instrumental resolution is suitable for crystallite size refinements. Additional crucial issues like contributions to the background and available q range are determined.